2011
DOI: 10.1097/mcg.0b013e3181e12ed3
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphataemic Osteomalacia in Patients on Adefovir Dipivoxil

Abstract: Fanconi syndrome results from generalised renal tubular toxicity and, owing to phosphate wasting can cause hypophosphataemic osteomalacia. Large clinical trials advocated the safety of adefovir dipivoxil at a daily dose of 10 mg, the standard dose given to patients with hepatitis B. We diagnosed Fanconi syndrome in conjunction with severe osteomalacia in 2 hepatitis B-positive patients on standard-dose adefovir therapy. The first patient was a 40-year-old male with a 5 month history of bone pain involving his … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 0 publications
3
41
2
Order By: Relevance
“…Nephrotoxicity associated with high-dose ADV typically has a late onset ([6 months) [15]. The time to onset of low-dose ADV-induced FS, based on case reports, ranges from a few months to [5 years [4][5][6][7][8][9][10][11][12]. In our patient, it took more than 2 years before the tubulopathy became apparent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nephrotoxicity associated with high-dose ADV typically has a late onset ([6 months) [15]. The time to onset of low-dose ADV-induced FS, based on case reports, ranges from a few months to [5 years [4][5][6][7][8][9][10][11][12]. In our patient, it took more than 2 years before the tubulopathy became apparent.…”
Section: Discussionmentioning
confidence: 99%
“…From the series of case reports so far, the time to resolution after cessation of ADV ranged from a few weeks to months [4][5][6][7][8][9][10][11][12]. A previous trial with high-dose ADV treatment showed a median time to resolution of renal dysfunction of 15 weeks, with the nephrotoxicity failing to resolve completely at 41 weeks after onset in 16 % of the patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acquired forms of Fanconi syndrome are caused by paraproteinemia, Sjögren syndrome, primary biliary cirrhosis (PBC) and drugs such as cisplatin [4][5][6]. Osteomalacia is a metabolic bone disease that leads to softening of the bones and can be caused by hypophosphatemia [7]. The clinical features of hypophosphatemic osteomalacia were slowly progressive distal muscle weakness, bone pain or even fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other nucleoside analogs, adefovir dipivoxil is characterized by low cost, low drug resistance and absence of cross-resistance, and has been applied widely in developing countries (4,5). However, renal toxicity is the most common adverse reaction associated with adefovir dipivoxil, and it has been reported to cause Fanconi syndrome (6)(7)(8), which is often misdiagnosed due to a dearth of knowledge among the majority of clinicians (9). In addition, some common manifestations of Fanconi syndrome, including systemic bone pain, osteoporosis and spontaneous fracture, are easily misdiagnosed as osteoarthrosis, osteoporosis and bone tumors in the early stages (9,10).…”
Section: Introductionmentioning
confidence: 99%